ANALYSIS OF THE INFLUENCE OF TRADE CREDIT INSURANCE SERVICES, ENTREPRENEURIAL ORIENTATION ON UMKM PERFORMANCE MODERATED BY GOVERNMENT SUPPORT Study on Trade Finance Services of PT. Bank Rakyat Indonesia (Persero) Tbk for Export MSMEs in Central Java Reg - Gigieh Perkasa; Yoestini (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
MSMEs have a strategic role in supporting national economic growth, especially through their contribution to the export sector. However, many exporting MSMEs face various challenges, such as international trade risks and limited entrepreneurial orientation, which can affect their performance. To overcome these challenges, trade credit insurance is present as one of the financial solutions that helps protect MSMEs from the risk of default. In addition, entrepreneurial orientation is an important factor in encouraging MSME competitiveness and innovation. In this context, government support is expected to moderate the influence of these two factors on improving the performance of exporting MSMEs. This study aims to analyze the effect of trade credit insurance and entrepreneurial orientation on the performance of export MSMEs, by considering government support as a moderating variable. This study was conducted on the trade finance service of PT. Bank Rakyat Indonesia (Persero) Tbk for export MSMEs in Central Java. Data collection was conducted through a survey of 150 respondents who were export MSME actors. Data analysis used multiple linear regression methods with statistical software. The results of the study indicate that trade credit insurance has a positive and significant effect on the performance of export MSMEs, as well as entrepreneurial orientation. However, government support does not moderate the effect of trade credit insurance on the performance of export MSMEs. On the contrary, government support is proven to strengthen the effect of entrepreneurial orientation on the performance of export MSMEs. This finding indicates that MSMEs that have access to trade credit insurance services and have a high entrepreneurial orientation can improve their export performance. Government support plays an important role in strengthening the positive impact of entrepreneurial orientation on export performance. This study contributes to the development of policies that support the performance of export MSMEs, especially in optimizing trade finance services and supporting programs from the government.